Corporate Fundamental Factors and Their Relation to Stock Prices: An Empirical Study in the Infrastructure and Transportation Sector - Sahlan Amiruddin (Athallah Publishing Globalindo, 2025)
This study aims to analyze the influence of fundamental company factors including return on equity, debt to equity ratio and price to book value on stock prices of infrastructure companies. The research sample was 15 companies in the infrastructure, utilities and transportation sectors listed on the IDX in 2019-2024 with a purposive sampling technique. Panel data was analyzed using SPSS 26 with an associative approach to obtain good regression results. The results of the study show that there is a combination of fundamental factors that influence stock price fluctuations. A significant positive correlation is shown by return on equity, debt to equity ratio and price to book value on changes in stock prices.